Religious Expression in the Digital Age: Shalawat Practices among Generation Z Indonesians - Baidawi, Baidawi; Daulay, Hamdan; Khamis, Kamarul Azman bin (Journal of Asian Wisdom and Islamic Behavior, 2024)
new religious trend on TikTok social media through religious expression played by urban Muslim millennials in the form of shalawat is taking place in the information age. This article aims to investigate the religious expression of urban Muslim millennials through shalawat impressions that often appear on the homepage. This research method uses descriptive qualitative through virtual ethnography approach. The data collection technique is through the selection of shalawat content on TikTok social media played by urban Muslim youth. The author chooses 3 shalawat contents that are considered viral and often circulate on TikTok social media. The results of this study show that TikTok media as a space for expressing the religiosity of urban Muslim millennials takes an important part in increasing social religious activities, fostering religious spirit and self-existence by openly displaying religious symbols, products and identities. The activism of young urban Muslims massively carries out religious rituals that are formed naturally in the form of virtual taklim assemblies that bring out passion in religion.